Comparison of Middle East News Framing by Al Jazeera and CNN - Azizah, Izza Afkarina; Ridhatullah, Nabila; Hikmah, Arina Nur; Sodikin (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the framing of Middle Eastern news coverage by two prominent international news outlets: Al Jazeera and CNN. Employing a qualitative methodology and Robert N. Entman’s framing theory, the research investigates how media from distinct cultural contexts construct narratives around key regional and global issues. Three case studies were selected to illustrate framing differences: (1) the Oscar win of the documentary “No Other Land”, (2) Saudi Arabia’s role in mediating global tensions between the United States, Russia, and Ukraine, and (3) the funeral of Aga Khan IV in Egypt. The findings reveal substantial contrasts in framing. Al Jazeera highlights themes of Palestinian suffering and humanitarian struggle in the “No Other Land” case, portrays Donald Trump positively in the mediation context, and emphasizes spiritual and humanitarian aspects of Aga Khan IV’s legacy. In contrast, CNN focuses on international reactions and controversies, presents a more critical view of Trump, and emphasizes global leadership without addressing spiritual or personal dimensions. The study concludes that media framing is not merely a reflection of events, but a deliberate construction shaped by the outlet’s cultural values, political interests, and intended audiences.